H3K4me3 changes occur in cell wall genes during the development of Fagopyrum tataricum morphogenic and non-morphogenic calli - Tomasiak, Alicja; Piński, Artur; Milewska-Hendel, Anna; Andreu Godall, Ignasi; Borowska-Żuchowska, Natalia; Morończyk, Joanna; Moreno-Romero, Jordi; Betekhtin, Alexander (Frontiers in Plant Science, 2024)
Chromatin immunoprecipitation (ChIP) is a powerful technique for studying the interplay between epigenetic modifications and the DNA regions of interest. In combination with sequencing, it can provide the genome-wide enrichment of the specific epigenetic mark, providing vital information on its involvement in the plethora of cellular processes. Here, we describe the genome-wide distribution of H3K4me3 in morphogenic and non-morphogenic callus of Fagopyrum tataricum. Levels of H3K4me3 were higher around the transcription start site, in agreement with the role of this mark in transcriptional activation. The global levels of methylation were higher in the non-morphogenic callus, which indicated increased gene activation compared to the morphogenic callus. We also employed ChIP to analyse the changes in the enrichment of this epigenetic mark on the genes coding for the cell wall proteins in both calli types during the course of the passage. Enrichment of H3K4me3 on cell wall genes was specific for callus type and particular gene expression,, suggesting that the role of this mark in the cell wall remodelling is complex, in agreement with regulation of the cell-wall components in the processes related to dedifferentiation and redifferentiation -leading to the acquisition of the morphogenic potential. This intricacy on the cell wall composition was supported by the immunohistochemical analysis of the cell wall epitopes' distribution of pectins and extensins.Together, these data give a novel insight into the involvement of H3K4me3 in the regeneration processes in F. tataricum in vitro callus tissue culture.